Crno more ili kraj sveta: Slojevita značenja simbola vode (Philologia, 2021)
The Black Sea is an example of the mythical boundary between the cosmos and chaos, the centre and periphery, the known and unknown. It reveals mythical meaning of the possibility to change the death for the life at its coast. The Black Sea is observed in the myth, history and literature. In the myth of Argonauts it represents the quest as a part of initiation. In Ovid’s destiny it is connected with his literature. The accent is on the contrast between the sea and Rome. The water boundary is also connected with motifs of exile and art in the novel The Last World by Christopf Ransmyr. The bond between the marginal place and the marginal character is crucial for the new interpretation of the mythic problem.